Upaya pencegahan stunting pada anak melalui edukasi gizi seimbang dan inovasi puding kelor - Patade, Agnes Erlita Distriani; Krisnawan, Gede Yoga Ditya; Ismail, Cahya; Salsabilah, Fitri; Rifai, Nur Faridha; Fransiska, Natalia; Bungaadjim, Indriyanti; Febrianti, Kirana; Amira, Siti Salwa; Tedengki, Steci Veronika; Umanata, Kadek; Ariani, Ariani; Keristiana, Ni Wayan; Ni Wayan Keristiana (Sasambo: Jurnal Abdimas (Journal of Community Service), 2025)
Stunting pada balita masih menjadi permasalahan kesehatan yang dipengaruhi oleh rendahnya pengetahuan gizi seimbang, keterbatasan ekonomi, serta kurangnya variasi pangan bergizi dalam rumah tangga. Program pengabdian ini bertujuan meningkatkan status gizi anak dan pengetahuan masyarakat dalam pencegahan stunting melalui pemberian makanan tambahan berbasis lokal berupa puding kelor. Kegiatan dilakukan melalui edukasi gizi seimbang, pembuatan dan pembagian puding kelor sebagai PMT. Hasil kegiatan menunjukkan adanya peningkatan absolut sebesar 11,1 atau setara dengan persentase peningkatan 16,3%. Kegiatan ini juga mendapat antusiasme tinggi dari para ibu yang aktif berpartisipasi dalam pembuatan puding kelor dan berkomitmen menerapkannya sebagai alternatif makanan bergizi bagi keluarga. Efforts to Prevent Stunting in Children Through Balanced Nutrition Education and Moringa Pudding Innovation Stunting among toddlers remains a significant public health concern influenced by limited knowledge of balanced nutrition, economic constraints, and a lack of dietary diversity within households. This community service program aimed to improve children's nutritional status and community knowledge in stunting prevention through the provision of locally based supplementary food in the form of Moringa pudding. The activities included balanced nutrition education, preparation, and distribution of Moringa pudding as complementary food. The results showed an absolute increase of 11.1 points, equivalent to a 16.3% improvement in participants’ knowledge. Moreover, the program received a high level of enthusiasm from mothers, who actively participated in the preparation of Moringa pudding and expressed commitment to adopting it as a nutritious alternative food for their families